2017
DOI: 10.1186/s12885-017-3300-y
|View full text |Cite
|
Sign up to set email alerts
|

Metformin produces growth inhibitory effects in combination with nutlin-3a on malignant mesothelioma through a cross-talk between mTOR and p53 pathways

Abstract: BackgroundMesothelioma is resistant to conventional treatments and is often defective in p53 pathways. We then examined anti-tumor effects of metformin, an agent for type 2 diabetes, and combinatory effects of metformin and nutlin-3a, an inhibitor for ubiquitin-mediated p53 degradation, on human mesothelioma.MethodsWe examined the effects with a colorimetric assay and cell cycle analyses, and investigated molecular events in cells treated with metformin and/or nutlin-3a with Western blot analyses. An involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Moreover, the same group showed that a simultaneous inhibition of the PI3K/mTOR pathway and Mdm2-p53 complex assembly (by nutlin-3) is potentially effective in AML ( Table 2 ) [ 82 ]. Even in mesothelioma, p53 pathway is often defective, thus leading to conventional treatments resistance, and Shimazu and his group investigated a possible mechanism of the combinatory effects between up-regulation of p53 levels and inhibition of the mTOR pathways, by nutlin-3 and metformin respectively [ 103 ]. Nevertheless, in this work the authors demonstrated that combination of metformin and nutlin-3a results in both additive and synergistic effects, probably due to heterogeneity of mesothelioma cells.…”
Section: Mtorc1 and Mtorc2 And Their Cross-talk With Other Pathwaymentioning
confidence: 99%
“…Moreover, the same group showed that a simultaneous inhibition of the PI3K/mTOR pathway and Mdm2-p53 complex assembly (by nutlin-3) is potentially effective in AML ( Table 2 ) [ 82 ]. Even in mesothelioma, p53 pathway is often defective, thus leading to conventional treatments resistance, and Shimazu and his group investigated a possible mechanism of the combinatory effects between up-regulation of p53 levels and inhibition of the mTOR pathways, by nutlin-3 and metformin respectively [ 103 ]. Nevertheless, in this work the authors demonstrated that combination of metformin and nutlin-3a results in both additive and synergistic effects, probably due to heterogeneity of mesothelioma cells.…”
Section: Mtorc1 and Mtorc2 And Their Cross-talk With Other Pathwaymentioning
confidence: 99%
“…HMM patients present poor therapeutic response due to traditional anticancer drug resistance, such as cisplatin and pemetrexed . Metformin, which is commonly used for the management of type II diabetes mellitus, has been suggested as an alternative anticancer drug . Recent studies have shown the potential therapeutic value of metformin in HMM cells, which is exerted through the inhibition of mTOR and cell cycle arrest .…”
Section: Introductionmentioning
confidence: 99%
“…20 Metformin, which is commonly used for the management of type II diabetes mellitus, has been suggested as an alternative anticancer drug. 21,22 Recent studies have shown the potential therapeutic value of metformin in HMM cells, which is exerted through the inhibition of mTOR and cell cycle arrest. 21 However, metformin treatment causes resistance in human breast cancer cells, although the precise mechanism has not been elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a retrospective study of 300 patients with type 2 diabetes and MPM did not shown any improvement to patient survival [ 105 ]. Meanwhile, metformin has been recently shown to inhibit MM cell proliferation when administered in combination with nutlin-3a (an inhibitor of ubiquitin-mediated p53 degradation) [ 106 ].…”
Section: Therapeutic Applications Based On Hippo Pathway Dysregulamentioning
confidence: 99%